THE ROLE OF ELEMENTS OF NATURE IN THE FORMATION OF SPORTS TOURISM SKILLS IN STUDENTS (Scientific journal of the Fergana State University, 2024)
In the article, the practical process of developing sports tourism skills in students based on the integration of physical education and natural geographical sciences, as well as the development of tourism in Uzbekistan in various other homogeneous places. Taking into account the social need for the further development of tourism, it was mentioned that the formation of tourism skills among the population of the Republic, in particular, in regional places, among young people in amalyot is one of the important pedagogical tasks.